UN and Muhammadiyah Cooperation in Eco-District Implementation to Address Environmental Issues in Yogyakarta - Nooresa, Avicenna Ismail (Jurusan Ilmu Hubungan Internasional, 2025)
Yogyakarta faces severe environmental issues, including a waste crisis and environmentally damaging mining activities. Muhammadiyah, a socio-religious organization, emphasizes environmental consciousness through its Environmental Assembly, aligning with SDG 13 on climate action. Meanwhile, the United Nations (UN), as a key SDG leader, is working with Yogyakarta's Regional Government on the Eco-District project, aiming to create sustainable urban areas by integrating environmental, economic, and social dimensions for an improved quality of life. This study explores the potential collaboration between the UN and Muhammadiyah to develop the Eco-District concept in Yogyakarta, leveraging the UN’s global environmental experience and Muhammadiyah’s extensive influence in Indonesian communities. Using a qualitative approach with a literature review, this research highlights strategies such as renewable energy promotion, waste management, green space expansion, and community education on sustainability. It assesses the planning, implementation, and outcomes of EcoDistrict projects, focusing on successes, challenges, and the value of multi-stakeholder partnerships for addressing complex environmental issues and fostering sustainable urban growth.